2021
DOI: 10.3389/fsurg.2021.756873
|View full text |Cite
|
Sign up to set email alerts
|

High Ligation of the Inferior Mesenteric Artery Induces Hypoperfusion of the Sigmoid Colon Stump During Anterior Resection

Abstract: Background: Anastomotic leakage (AL) after colorectal surgery is associated with insufficient vascular perfusion of the anastomotic ends. This study aimed to evaluate the effect of high vs. low ligation of the ileocolic artery and inferior mesenteric artery, respectively, on the vascular perfusion of the bowel stumps during ileocecal resection (ICR) and anterior rectal resection (AR).Methods: We retrospectively evaluated patients who underwent ICR or AR between 2016 and 2020. Real-time indocyanine green fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…For instance, Dworlin and Allen‐Mersh demonstrated significant reduction in sigmoid colon serosal blood flow following ligation of the IMA [48]. Three other studies have yielded similar findings [46, 49, 50]. Whether the reduction in colonic perfusion after high ligation of IMA confers a higher risk of anastomotic leakage post‐colectomy is yet to be demonstrated [51, 52].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Dworlin and Allen‐Mersh demonstrated significant reduction in sigmoid colon serosal blood flow following ligation of the IMA [48]. Three other studies have yielded similar findings [46, 49, 50]. Whether the reduction in colonic perfusion after high ligation of IMA confers a higher risk of anastomotic leakage post‐colectomy is yet to be demonstrated [51, 52].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study performed real-time indocyanine green fluorescence angiography to measure fluorescence time as a marker of blood flow in the proximal and distal stumps before anastomosis. The results showed that IMA high ligation significantly prolonged fluorescence time in the sigmoid colon during anterior rectal resection compared with low ligation, which indicates that IMA high ligation induced significant colon stump hypoperfusion ( 4 ). This finding possibly explains why IMA high ligation resulted in a high rate of AL.…”
Section: Discussionmentioning
confidence: 99%
“…High ligation of IMA with D3 lymph node dissection can improve the survival rate of patients ( 2 , 3 ). However, insufficient perfusion of stumps after high ligation of IMA may lead to anastomotic ischemia ( 4 6 ). The blood supply of the proximal and distal stumps of anastomosis is an important factor affecting its healing.…”
Section: Introductionmentioning
confidence: 99%
“…According to anatomy, HT may have a better oncological outcome due to a more extended apical lymph node dissection, while LT may have a better anastomotic blood supply due to LCA preservation. “HT or LT” has been a hot research topic in recent years [ 14 , 19 – 22 ]. Although many previous studies believe that the two ligation methods had little effect on the oncological outcomes, we still could not deny the importance of D3 lymph node dissection because of the low-grade quality evidences of these studies and the low rate of apical lymph node metastasis [ 11 , 21 25 ].…”
Section: Discussionmentioning
confidence: 99%